Association of Haemoglobin and C-Reactive Protein level with Different Risk Factors among Acute Coronary Syndrome Patients - Morshed, Md Mahboob; Islam, Md Joynul; Ashadullah, ATM; Hussain, Khondker Shaheed; Haque, Mohammad Ahtashamul (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: Different risk factors may be related with the haemoglobin and CRP level among the acute coronary syndrome patients. Objective: The purpose of the present study was to see the association of haemoglobin and CRP level with different type of risk factors among the acute coronary syndrome patients. Methodology: This cross-sectional study was conducted in the Department of Cardiology at Mymensingh Medical College, Mymensingh, Bangladesh from December 2010 to November 2011 for a period of two (02) years. Patients of ACS who were presented within 12 hours of chest pain were included as study population. Study population were categorized in four groups according to the level of hemoglobin and C-reactive protein. Age, cardiovascular risks factor, history, family history of cardiovascular disease, treatment history and ECG were taken during admission. Blood sample was collected for baseline laboratory investigations like Troponin-I, Random Blood Sugar (RBS), Blood urea, Serum creatinine, lipid profile, Hemoglobin & CRP level. Sample were then send to standard laboratory/Biochemistry department of MMCH. Result: The mean age of the population was 52.18±8.88 years. Smoking was the highest percentage in Group 1 which was 54(50.0%) cases (P=0.001). Hypertension was found most common in group 1 (47.6%), Group 2 (33.3%), Group 3 (10.7%) and Group 4 (8.3%). Smoking (p=0.001) and hypertension (p=0.016) was found statistically significant. Diabetes was found in Group 1 (37.7%), Group 2 (43.5%), Group 3 (11.6%) and Group 4 (7.2%). Group 1 (50%) and Group 2 (50%) patients were dyslipidaemic. Family history of IHD was present group-1 (36.8%), Group 2 (44.7%), Group 3 (73.2%) and Group 4 (53%). Among the smoker patient 65.6% cases had CRP level ˃12 mg/l; 39.8% cases had CRP level ˂12mg/L. Among the nonsmoker 34.4% cases had CRP level ˃12mg/l and 60.2% cases had CRP level ˂12mg/L. The finding was statistically significant. Conclusion: In conclusion haemoglobin and CRP level is associated with different type of risk factors among the acute coronary syndrome patients. Journal of National Institute of Neurosciences Bangladesh, 2019;5(2): 156-160